Experimental results from a linear wave power generator connected to a resonance circuit. Issue 4 (13th July 2012) - Ekergård, Boel; Boström, Cecilia; Hagnestål, Anders; Waters, Rafael; Leijon, Mats
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>